Students’ Learning: Exploring the Role of Teacher Favoritism and Classroom Management - Ghulam Muhammad; Sadia Noor Awan; Shaharyar Sheikh; Humaira Anwer Ali; Bilal Ahmed; Iqra Qambrani; Umair Muhammad Khan (Journal of Management Practices, Humanities and Social Sciences, 2023)
Our research endeavors to investigate the correlation between favoritism and student psychology, concurrently exploring the potential mediating influence of classroom management. We gathered primary data from 120 students in higher educational institutions in Karachi, Pakistan. The analysis, conducted using Smart PLS v.3.3.5 and IBM SPSS v.26, revealed noteworthy impacts of favoritism on both students, Learning psychology, and classroom management. However, no significant relationship emerged between classroom management and students' psychology. Furthermore, the study indicated that classroom management does not serve as a mediating factor in the relationship between favoritism and students' learning psychology. The findings underscore the significance of teachers evaluating their behavior and intentions in the classroom, given that the overall class environment is shaped by their actions. Favoritism was identified as a detrimental factor influencing students’ learning psychology, resulting in diminished self-esteem and motivation. The study emphasizes the necessity of eliminating favoritism to promote equality among students and stimulate their active participation.